Influence of comorbidity on working memory profile in dyslexia and developmental coordination disorder. Issue 7 (8th August 2020) - Maziero, Stéphanie; Tallet, Jessica; Bellocchi, Stéphanie; Jover, Marianne; Chaix, Yves; Jucla, Mélanie
ABSTRACT: Objective: Many studies report a deficit in working memory in children with Developmental Dyslexia (DD) and Developmental Coordination Disorder (DCD) compared to children with Typical Development (TD). In this study, we questioned the working memory profile of children with co-occurring Developmental Dyslexia and Developmental Coordination Disorder (DD-DCD). First, we hypothesized that children with DD would have a more substantial deficit in verbal working memory, while children with DCD would have a more substantial deficit in visuospatial working memory. For the comorbid group, we postulated a deficit in both the verbal and visuospatial domains. Second, we determined whether we could correctly distinguish between the four groups based on their working memory profiles. Method: 47 children with DD, 22 children with DCD, 27 children with DD-DCD, and 42 TD children aged from 7.6 to 12.6 years were tested on the phonological loop, the visuospatial sketchpad, and the central executive using the Digit Span and Wechsler's Block-tapping tests. Results: Children with DD had a deficit in verbal working memory including a specific deficit in the phonological loop and children with DCD had a deficit in visuospatial working memory. Comorbid children had poorer performance in verbal working memory (like group with DD) and in visuospatial working memory (like group with DCD). Exploratory cluster analysis resulted in four subgroups: (1) one cluster with good working memory performance made up of most of the TD children; (2) one cluster with a phonological loop deficit mainly made up of the children with DD; (3) one cluster with poor visuospatial working memory capacities mostly made up of the children with DCD (± DD) and (4) one cluster with average performance made up of children from all the groups. Conclusion: Our results underline the importance of taking comorbidity into account when testing working memory in children with learning disabilities.